Aedes albopictus in an area of Misiones, Argentina - Nicolás Schweigmann; Darío Vezzani; Pablo Orellano; Jorge Kuruc; Rolando Boffi
Until early 1998 the presence of Aedes albopictus had never been detected in Argentina. During April of the same year, few individuals of this species were recorded in 33 breeding sites found in 25 out of 161 inspected houses in the city of Eldorado, Province of Misiones. The homogeneous spatial distribution of the proliferation foci suggests the existence of a generalized infestation in this locality during the study period.